PROSPECTIVE EVALUATION OF HBV, HCV, HIV AND SYPHILIS PREVALENCE IN Β-THALASSEMIA MAJOR PATIENTS BEFORE AND AFTER BLOOD TRANSFUSIONS. - Shahzaib Haider; Amna Kausar; Aneesa Murtaza; Ayesha Kanwal; Muhammad Jabran; Faika Arooj; Zunaira Saleem; Hafiz Asif Muhammad Ali (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Abstract  Patients with β-thalassemia (major) frequently require blood transfusions, which puts them at increased risk of transfusion-related infections (TTIs). The transfusion transmitted infections are HCV, HBV, HIV and Syphilis. The main victims of TTIs are β-thalassemia (major) patients because they require regular blood transfusions which are very necessary for the survival of patients. The major complications are HCV, HBV, HIV and Syphilis as their causative agents are transferred consciously or unconsciously to the recipients. To check the infection rates in β-thalassemia (major) patients before and after blood transfusion is the main objective of this study. The other objective is to check the reliability of Immunochromatography Technique (ICT) and Chemiluminescence Immunoassay (CLIA) in detecting these infections. A total of 421 β-thalassemia (major) patients were selected initially but 21 patients were reactive with HCV so they excluded from study. The remaining 400 β-thalassemia (major) patients were selected for the study. Blood samples were collected from patients before blood transfusion and then after 3 months of 1st transfusions and then 6 months of 2nd blood transfusions and results were analyzed. The serum/plasma was separated by centrifugation and stored in Ultra-low at -70°C until further processing. The results showed an increased in the prevalence of infections among patients over time. Initially, all β-thalassemia (major) patients were free of infections. After the three months of 1st blood transfusions 3.5% of infections were detected in β-thalassemia (major) patients using Immunochromatography Technique (ICT) and 4% detected using Chemiluminescence Immunoassay (CLIA). The prevalence of Hepatitis C was 3.5% which is greater than other TTIs. The overall infection rates were increased after 6 months of blood transfusions. The prevalence of HCV increased by 4% and Hepatitis B (HBV) 0.50%. HIV was detected only in case of ICT technique but the CLIA did not confirm it. The specific analysis of age indicated a high infections rate of Hepatitis C was found in 11-20 years age group compared to other age groups. These results indicated that transfusions transmitted infections were increased with multiple transfusions. The study concluded that β-thalassemia patients are at high risk of transmitted transfusion infections. Hepatitis C is more prevalent infections in β-thalassemia patients. Infection rates were increased from 4% to 4.5 with successive transfusions. Two techniques ICT and CLIA were used for the detection of TTIs. Both techniques were effective for detecting TTIs but CLIA is more reliable than ICT due to capturing weak positive infectious agents which were not detected with ICT.Chi square analysis revealed that there is no significant association between blood transfusions with transmitted transfusion infections. Future studies should be focused on the development of more advance and sensitive techniques for the detection of transmitted transfusion infections in β-thalassemia patients. Proper infections control practices and awareness about thalassemia will be helpful to minimize the infections rates.